Palm Kernel Oil Blends as Suppository Bases in the Delivery of Aspirin - Noordin, M.I.; Chung, L.Y. (2007)
Rectal delivery of drugs has been proven to be effective in terms of drug absorption and distribution comparable with other routes such as oral, buccal, sublingual or even nasal. In this study, two new suppository bases were developed using combinations of locally sourced hydrogenated palm kernel oil, hydrogenated palm kernel stearin and hydrogenated palm kernel olein with mixtures of stearic acid and glyceryl monostearate. When formulated with aspirin, these bases produced suppositories with acceptable characteristics. These aspirin suppositories were tested on twelve healthy subjects after an approval from the Medical Ethics Committee, University of Malaya had been procured. We quantified aspirin from the urine samples of the subjects to determine the relative availability of the different suppository preparations relative to an oral dose. The excretion of salicylic acid, one of the metabolite of aspirin in human urine taking aspirin was quantified. The F value was found to range from 1.16 to 1.38. Hence, the excretion results showed that these palm kernel oil blends are suitable suppository bases.